Teacher Burnout at Secondary Level of Education in Haryana - Sahni, Madhu; Sharma, Anju (INDIAN EDUCATIONAL REVIEW, 2015)
The purpose of the present investigation was to assess the level of burnout and to study the influence of personality, educational qualification, length of service and their various interactions on burnout among secondary school teachers. The sample comprised 480 secondary school teachers selected randomly from 24 secondary schools of Haryana. Data were analysed using three way ANOVA (2×2×2factorial design) and t-test. Results indicated that (i) the secondary school teachers experienced high level of burnout; (ii) there is significant independent effect of variables viz. personality, educational qualification and length of experience on burnout among secondary school teachers; and (iii) there is significant two factor and three factor interactive effect of variables on burnout among secondary school teachers.